Alcohol Consumption Habits and Perceptions among Students - Zhubi, Mimoza; Zhubi, Dren; Bajraktari, Agron (Mediterranean Journal of Social Sciences, 2020)
For a long period of time, alcohol consumption has been considered a shortcut to relieve stress and modify behavior in order to have a better time and provide a pleasant company in the eyes of other fellow companions. This is peculiarly valid for young ages who occupy a more active social life. The habit of alcohol consumption has been repeatedly evaluated and each time a different factor has appeared to play a role in its development. Alcohol beverages are consumed by students at different rates in different countries. High-income countries seem to have a wider range of consumption among students, even though their rules in alcohol consumption seem to be stricter. Meanwhile, fewer evaluations have been provided in this aspect in low-income countries. What seems to be interesting is that different circumstances that accompany living in low-income countries may obtain a valuable set of results that would provide a solid comparison between alcohol consumption habits between students in low-income countries and high-income countries. The use of such data may facilitate the implementation of alcohol policies and regulations accordingly.